Specific features of psychopathological manifestations in criminal clozapine intoxications - D. G. Slyundin; A. S. Livanov; V. V. Anuchin; A. G. Merkin; I. G. Bobrinskaya; E. V. Gutova (Неврология, нейропсихиатрия, психосоматика)
Criminal clozapine (azaleptin, leponex) intoxications are notified very frequently (as high as 99.7% of all criminal intoxications) and have virtually supplanted earlier predominant clofelin poisoning.Objective: to identify the characteristic clinical features of acute clozapine intoxications to make their differential diagnosis with the similar acute states that are most frequently encountered at the prehospital stage.Subjects and methods. A total of 4757 patients diagnosed as having criminal clozapine intoxication, followed at the Toxicology Unit, Prof. A.A. Ostroumov City Clinical Hospital Thirty-Three, in 2003 to 2009, were examined and their case histories were analyzed. There were 4474 (94.05%) men and 283 (5.95%) women. The patients aged less than 21 years were 10.6%; those of 21 to 60 and over 60 years of age were 88.7 and 0.7%, respectively. None of them had been followed by a psychiatrist and had systematically taken any psychotropic drugs. Most (54%) of the victims were the capital's guests. Clinical and laboratory studies were used to examine the patients. The pattern and situational features of the intoxication were revealed; the leading clinical syndrome and its degree were established. The group patients' conditions were rated on admission, by applying the integral APACHE-2 scale; the Glasgow coma scale was used to determine the degree of impaired consciousness. The patients' status was analyzed by clinico-anamnestic and clinicopsychopathological studies, as well as by a neuropsychological test after abolishing sopor and coma and then on days 3 and 5 of inpatient treatment.Results. The interval between intoxication to the arrival of an emergency team (ET) was 30 min to 5 hrs (mean 1.43+0.68 hrs). During this period, the level of consciousness reduced with on-going agent absorption, changing from torpor to sopor or coma. ET sent 98.3% of the patients to hospital for the diagnoses of alcoholic intoxication, alcoholic surrogate, opiate, or clofelin poisoning, closed brain injury, or coma of unknown etiology. On admission, the patients' condition was rated as severe in 98.5% and moderate in 1.5%. Stage I intoxication was present in 17 (0.35%) patients; Stage IIA in 4579 (96.25%), IIB in 75 (1.57%), III in 1 (0.02%), and IV in 85 (1.86%). The patients were found to have peculiar mnestic disorders. Intensive care comprised complex detoxification, infusion therapy, and vitamin therapy; respiratory support was also made in the absence of respiratory disorders. Prominent in the therapy was the use of the antidote intravenous aminostigmine and galantamine bromide in a dose of 2-3 mg. During therapy, there was consciousness recovery for an average of 1.22+0.68 hours with psychomotor excitement developing within 40-90 min and giving way to the significant asthenic syndrome that preserved within 16-30 other hours. Three patients died; 2 of them were patients with Stage IIB with comorbidities.Conclusion. Criminal clozapine intoxications are distinguished by the fact that they generally occur in the street (97.75%) or public area; the intoxication victims are socially preserved patients; moreover, their money and valuables practically always disappear. In addition, the intoxications are characterized by the rapid development of severe disorders of consciousness, a short-term toxicogenic phase, and a rarity of severe in-hospital complications (from 1.2% in Stage IIA to 3.5% in Stage IIB; no bronchopulmonary complications in Stages I and IV). Fatal outcomes in criminal intoxications are recorded in 00.11% of cases whereas those are in 10-18%. The specific features of the course of criminal clozapine intoxications seem to lie in the combined effects of clozapine and ethanol on the central nervous system and their synchronous metabolism.